OPTIMIZING THE ROLE OF INTERNAL AUDIT AND ACCOUNTING LITERACY TO PROMOTE FINANCIAL ACCOUNTABILITY OF WOMEN'S MSMES: A CASE STUDY IN ACEH PROVINCE - Arliansyah; Wahyuddin; Falahuddin; Hanif; Fuadi; Muhammad Multazam (RADJA PUBLIKA, 2025)
This study aims to analyze the strategic role of internal audit and accounting literacy in improving financial accountability among women-owned Micro, Small, and Medium Enterprises (MSMEs) in Aceh Province, Indonesia. Financial accountability is viewed as the ability of MSMEs to present transparent, accurate, and reliable financial information to stakeholders such as investors, financial institutions, and partners. The study employs a mixed-methods approach, combining quantitative analysis with qualitative interviews and observations. The sample consists of 75 women entrepreneurs selected through purposive sampling. Data were collected using structured questionnaires, in-depth interviews with key institutions (Cooperatives and MSME Office, BPKP, OJK, and local NGOs), and field observations. Quantitative results indicate that both internal audit and accounting literacy have significant positive effects on financial accountability. The regression analysis shows that accounting literacy (β = 0.736, Sig. = 0.001) contributes more strongly to financial accountability than internal audit (β = 0.085, Sig. = 0.005). Simultaneous testing (F = 11.630 > F-table = 2.712) confirms that these two factors jointly affect financial accountability. The coefficient of determination (R² = 0.297) implies that 29.7% of the variance in financial accountability is explained by both variables. Qualitative findings reinforce that regular bookkeeping, simple internal control practices, and contextual financial education significantly enhance transparency and accountability. The study concludes that the synergy between internal audit and accounting literacy forms a crucial foundation for transparent and accountable financial governance in women's MSMEs. Policy implications suggest that local governments, financial regulators, and NGOs should collaborate to develop gender-sensitive financial literacy programs and simplified internal audit models that are adaptable to small-scale enterprises.